Cosmologia de Teorias de Gravitação com Dependência de Escala. - Santos, Felipe de Melo (2021)
The extensions of general relativity with scale-dependent G and Λ couplings have been proposed for different motivations, but inspired, in particular, by non-trivial effects of the application of a renormalization group to the gravitation. We will consider the cosmological scenario of this framework from two perspectives: developing a self-consistent action, with the necessary information to describe the dynamic of the model; and from a numerical and observational point of view, considering the viability of the proposal from several cosmological data. Regarding the theoretical aspects of dynamical principles, the framework is such that the background evolution is subject to the same equations that govern the cosmological background of the standard model (ΛCDM), but the perturbations have corrections that depend on the scalar factor coming from the perturbation of the metric, present in other non-cosmological scenarios, and on a secondary scalar originated from consistency conditions and dependent on the trace of the energy-moment tensor. For the phenomenology of this picture, we evaluated via MCMC the data from fσ8, Supernovas type Ia, baryonic acoustic oscillations, distortion in redshift space, and data from the cosmic background radiation. Our first analysis with a complete data set for a particular case in this frame suggests small deviations in the parameters of ΛCDM.